2015
DOI: 10.1111/1754-9485.12275
|View full text |Cite
|
Sign up to set email alerts
|

Is modern external beam radiotherapy with androgen deprivation therapy still a viable alternative for prostate cancer in an era of robotic surgery and brachytherapy: A comparison of Australian series

Abstract: Modern EBRT is at least as effective as modern Australian surgical and brachytherapy techniques. All patients considering treatment for localised prostate cancer should be referred to a radiation oncologist to discuss EBRT as an equivalent option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…In addition, 46 % of the cases were treated with IMRT alone, Table 3 Comparison of the backgrounds between IMRT and 3D-CRT cases IMRT intensity-modulated radiation therapy, 3D-CRT three-dimensional conformal radiation therapy, iPSA initial (pretreatment) prostate-specific antigen, NA-HT neoadjuvant hormonal therapy, PSA@S-HT prostate-specific antigen when salvage hormonal therapy was initiated a D'Amico's risk classification which is no longer the standard approach to EBRT for both intermediate-risk and high-risk prostate cancer. When focusing on the outcomes of high-dose IMRT combined uniformly with HT for cohorts of patients with intermediate-and high-risk localized prostate cancer, reports on outcomes up to 5 years are now available [18][19][20][21]. In this article, we report the long-term outcomes of high-dose IMRT combined with short-term NA-HT for patients with clinically localized prostate cancer over a 10-year median follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 46 % of the cases were treated with IMRT alone, Table 3 Comparison of the backgrounds between IMRT and 3D-CRT cases IMRT intensity-modulated radiation therapy, 3D-CRT three-dimensional conformal radiation therapy, iPSA initial (pretreatment) prostate-specific antigen, NA-HT neoadjuvant hormonal therapy, PSA@S-HT prostate-specific antigen when salvage hormonal therapy was initiated a D'Amico's risk classification which is no longer the standard approach to EBRT for both intermediate-risk and high-risk prostate cancer. When focusing on the outcomes of high-dose IMRT combined uniformly with HT for cohorts of patients with intermediate-and high-risk localized prostate cancer, reports on outcomes up to 5 years are now available [18][19][20][21]. In this article, we report the long-term outcomes of high-dose IMRT combined with short-term NA-HT for patients with clinically localized prostate cancer over a 10-year median follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently estimated that one-half to two-thirds of cancer patients receive radiation therapy in curative or palliative settings during their disease [1,2]. Radiotherapy is a therapeutic approach with a very high potential for local control: ionizing radiation is equally as effective as surgery in curing prostate [3,4], laryngeal [5], cervical [6], and anal cancers [7]. However, and despite very effective radiation-induced cancer cell elimination and local tumor control, not all malignant tumors respond equally to radiation therapy: some patients do not derive clinical benefit from it because their tumors are constitutively insensitive to therapeutic doses of ionizing radiation, or are able to acquire such insensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…This final stage of the class solution demonstrated that 89% of prostate patients met treatment criteria outright (S. Greenham, personal communication). Further research is required to determine whether prostate class solutions can maintain or improve upon the clinical and patient-reported outcomes 5,6,15 of dose-escalated image-guided IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were volumed using magnetic resonance imaging (MRI) and computed tomography (CT) fusion 4 and treated to 81 Gy as previously described. 5,6 Planning criteria and OAR constraints are summarised in Tables 1 and 2 and were based on evidencebased guidelines (EviQ recommendations). 7 Minor violations were acceptable when all reasonable efforts to achieve ideal constraints had been made.…”
Section: Methodsmentioning
confidence: 99%